The development of Afrocentricity: A historical survey (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The origin of the Afrocentric philosophy cannot be established with certainty. The most influential book advocating it was published in 1954. Marcus Garvey was one of the most influential propagators of the ideology. Afrocentricity as an idea and a philosophy gained momentum during the Civil Rights Movement in the United States of America. It was in the Temple University School of Scholars, frequently referred to as the Temple Circle, where the philosophy was institutionalised. The abstract noun “Afrocentricity” dates to the 1970s and was popularised by Asante during the 1980s, when he developed epistemological and methodological foundations for an Afrocentric curriculum based on an African perspective but aiming at global understanding.1 The approach proposes that blacks (at home and abroad) must look at knowledge from an African perspective. It suggests looking at matters at hand from an African viewpoint; that we misunderstand Africa when we use viewpoints and terms other than that of the African to study Africa. When Africans view themselves as centred and central in their own history, they see themselves as agents, actors, and participants rather than as marginal and on the periphery of political or economic experience. Although not the antithesis of Eurocentrism, Afrocentrism has become the most explosive and controversial subject, with both black and white scholars squaring off on its viability and non-viability. Mary Lefkowitz, Stanley Crouch, and Anthony Appiah are some of the main opponents of the Afrocentric idea. The Western dogma which contends that Greeks gave the world rationalism effectively marginalises those who are not European and becomes the leading cause of the disbelief about African achievements. This paper traces the origin of Afrocentricity and describes the nature and propositions put forward by Afrocentrists that challenge the traditional Eurocentric perspective. This paper provides answers to the questions of why, when, where, and who were the main people behind its emergence. The paper also aims at outlining the main arguments why the approach should become part of academic debates. Afrocentricity, however, like other approaches, is not without pitfalls; for this reason the paper examines criticism levelled against it and responses thereto.
Keywords: Afrocentricity; Eurocentricity; Africa; History; Ancient Egypt; Ancient Greece; Slavery; Colonialism; Racism